2008
DOI: 10.1038/cdd.2008.145
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel cyclin required for the intrinsic apoptosis pathway in lymphoid cells

Abstract: We have identified an early step common to pathways activated by different forms of intrinsic apoptosis stimuli. It requires de novo synthesis of a novel cyclin, cyclin O, that forms active complexes primarily with Cdk2 upon apoptosis induction in lymphoid cells. Cyclin O expression precedes glucocorticoid and c-radiation-induced apoptosis in vivo in mouse thymus and spleen, and its overexpression induces caspase-dependent apoptosis in cultured cells. Knocking down the endogenous expression of cyclin O by shRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Ccno in mouse lymphoid cells can bind and activate CDK2 to respond to DNA damage-induced intrinsic apoptosis stimuli. When Ccno was knocked down, DNA damageinduced apoptosis could be abrogated [21].…”
Section: Introductionmentioning
confidence: 99%
“…Ccno in mouse lymphoid cells can bind and activate CDK2 to respond to DNA damage-induced intrinsic apoptosis stimuli. When Ccno was knocked down, DNA damageinduced apoptosis could be abrogated [21].…”
Section: Introductionmentioning
confidence: 99%
“…Downstream from the MCIDAS/E2F complex also lies CCNO ( Fig. 1) (Stubbs et al 2012;Ma et al 2014;Wallmeier et al 2014), a cyclin-like protein first shown to be involved in oocyte meiosis resumption and apoptosis (Roig et al 2009;Ma et al 2013), and then shown to be expressed in MCC progenitors in the Xenopus skin and in the mouse brain, airways, and oviducts (Stubbs et al 2012;Funk et al 2015;Amirav et al 2016). Although its partners and molecular function remain to be determined, CCNO mutations or depletion lead to defects comparable to the C-MYB phenotype: defects in BB amplification, docking, and ciliogenesis Funk et al 2015).…”
Section: Downstream Effectors Of the MCC Differentiation Programmentioning
confidence: 99%
“…Therefore, it is not surprising that several studies have assigned CCNO a role in multiciliogenesis and mucociliary disorders [73][74][75][76][77][78] and infertility [79]. CCNO has also been shown to promote apoptosis in lymphoid cells [80].…”
mentioning
confidence: 99%